2022
DOI: 10.1038/s41467-022-34124-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of water structure around interlayer ions for ion storage in layered double hydroxides

Abstract: Water-containing layered materials have found various applications such as water purification and energy storage. The highly structured water molecules around ions under the confinement between the layers determine the ion storage ability. Yet, the relationship between the configuration of interlayer ions and water structure in high ion storage layered materials is elusive. Herein, using layered double hydroxides, we demonstrate that the water structure is sensitive to the filling density of ions in the interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Layered double hydroxides (LDHs) are layered compounds that have been known for a long time but have recently been attracting much attention owing to their wide variety of advanced functions. Layered nickel hydroxides and Fe-containing LDHs are promising as electrode catalysts for water oxidation. , Solid base catalysis for organic chemical reactions, photocatalysis for CO 2 reduction, , and ion storage materials are also important research fields for green chemistry and sustainable energies. Recently, developed techniques have enabled the synthesis of LDH nanomaterials, such as nanocrystals and nanosheets .…”
Section: Introductionmentioning
confidence: 99%
“…Layered double hydroxides (LDHs) are layered compounds that have been known for a long time but have recently been attracting much attention owing to their wide variety of advanced functions. Layered nickel hydroxides and Fe-containing LDHs are promising as electrode catalysts for water oxidation. , Solid base catalysis for organic chemical reactions, photocatalysis for CO 2 reduction, , and ion storage materials are also important research fields for green chemistry and sustainable energies. Recently, developed techniques have enabled the synthesis of LDH nanomaterials, such as nanocrystals and nanosheets .…”
Section: Introductionmentioning
confidence: 99%
“…In brief, high nitrate ion intercalation in the dilute regime is driven by enhanced interlayer binding forces, while the capacity that remains at a low level in concentrated regime is due to weakened interlayer binding forces owing to further nitrate ion inclusion into the interlayer spaces. Remarkably, our previous study suggested that this transformation in the interlayer environment of the LDHs structure includes a 2D to 3D transformation of the hydrogen-bonding network between the interlayer ions and water molecules …”
mentioning
confidence: 93%
“…QCM-D is an effective in situ measurement tool for understanding the ion dynamics in matter. From the change in the frequency (Δ f ) value, the real-time mass transfer of inter­(de)­intercalating ion in association with water can be monitored. Importantly, dissipation (Δ D ) monitoring has been long utilized for studying the dynamic deformation behaviors accompanying viscoelastic change in water-containing soft matter. , The viscoelasticity of the LDHs represents the overall interlayer binding force . Therefore, by simultaneously monitoring the Δ D values and Δ f , the dynamic change in the interlayer binding force along with mass transfer of LDHs upon nitrate intercalation is studied (Figure b).…”
mentioning
confidence: 99%
See 2 more Smart Citations